VEGF 936C > T Polymorphism and Association of BI-RADS Score in Women with Suspected Breast Cancer - Wehrschuetz, M. (Libertas Academica, 2009)
PURPOSE: Vascular endothelial growth factor (VEGF) is a potent regulator of angiogenesis and thereby involved in the development and progression of solid tumors. A 936C > T polymorphism in the VEGF gene has been associated with reduced VEGF plasma levels. Purpose of the present study was to analyze the potential association between VEGF genotype and radiological appearance of breast lesions by mammography. MATERIALS AND METHODS: Fifty two women with 54 suspected breast lesions were analyzed by the use of mammography with the standard breast imaging reporting and data systems (BI-RADS). Germline VEGF genotype was determined in all subjects by allele-specific digestion of amplification products. An open biopsy was performed on all lesions. RESULTS: VEGF CC, CT and TT genotypes were found in 41 (79%), 9 (17%) and 2 (4%) patients. By mammography 26, 16 and 12 suspected breast lesions were classified as BI-RADS scores 3, 4 and 5, respectively. Both carriers of the TT genotype were classified as BI-RADS 5, whereas among CT or CC carriers, BI-RADS scores 3, 4 and 5 were found in 26, 16 and 10 subjects (P < 0.026). CONCLUSION: The VEGF 936C > T polymorphism seems to be associated with a high BI-RADS score in women with suspicious breast lesions.